2008
DOI: 10.1074/jbc.m802821200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS5A Protein Down-regulates the Expression of Spindle Gene Aspm through PKR-p38 Signaling Pathway

Abstract: Hepatitis C virus often causes persistent infection and hepatocellular carcinoma. Studies have demonstrated the roles of viral nonstructural protein 5A (NS5A) in the induction of chromosome aneuploidy, but the molecular mechanisms are not clear. In this study, hydrodynamics-based in vivo transfection was applied to a mouse system. Mouse hepatocytes that successfully expressed NS5A protein were isolated by laser capture microdissection. Gene expression profiles of the NS5A-expressing hepatocytes were examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…HBV basal core promoter mutations (A1762T/G1764A) are found to be associated with the occurrence of HCC in several cross-sectional (Baptista et al ., 1999; Kao et al ., 2003) and longitudinal studies (Chou et al ., 2008; Fang et al ., 2008; Wu et al ., 2008; Yuan et al ., 2009). The REVEAL-HBV study from Taiwan found that the multivariable-adjusted hazard ratio of developing HCC was 1.73 for basal core promoter mutations and that the risk was highest among participants infected with genotype C HBV and who harbored the precore 1896 variant and mutations for the basal core promoter (Yang et al ., 2008).…”
Section: Hbv Proteinsmentioning
confidence: 99%
“…HBV basal core promoter mutations (A1762T/G1764A) are found to be associated with the occurrence of HCC in several cross-sectional (Baptista et al ., 1999; Kao et al ., 2003) and longitudinal studies (Chou et al ., 2008; Fang et al ., 2008; Wu et al ., 2008; Yuan et al ., 2009). The REVEAL-HBV study from Taiwan found that the multivariable-adjusted hazard ratio of developing HCC was 1.73 for basal core promoter mutations and that the risk was highest among participants infected with genotype C HBV and who harbored the precore 1896 variant and mutations for the basal core promoter (Yang et al ., 2008).…”
Section: Hbv Proteinsmentioning
confidence: 99%
“…For DMSO treatment, HuS-E/2 cells were seeded at 60% confluence for 18 h and DMSO was added to a final concentration of 2% (vol/ vol), and then the DMSO-containing culture medium was changed every 3 days for 10 to 12 days, when the differentiated HuS-E/2 cells were used for HBV infection experiments in the continued presence of 2% DMSO. Cells of the cell lines Huh7 (a human hepatoma cell line), HepG2 (a human hepatocellular carcinoma cell line), and 293 (a human embryonic kidney cell line) were maintained as described previously (54).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, the expression of 31 upregulated and 7 downregulated genes were positive both in HCC and liver-cirrhosis nodules (Nagai et al, 2004). Wu et al showed that the NS5A protein downregulated the expression of the mitotic spindle protein ASPM and induced an aberrant mitotic cell cycle, which was associated with chromosome instability and subsequently HCC (Wu et al, 2008). Wu et al studied human osteopontin positive and negative HCC tissues and found some tumor-related genes, such as SMR3B, MUC7, EPHA5, SPP1, and CLDN10 to have significantly higher expression in osteopontin positive HCC than in osteopontin negative HCC (Wu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…If so, they may be useful as candidate genes for the diagnosis and treatment of HCC. The ASPM (abnormal spindle-like microcephaly) gene that encodes a mitotic spindle protein is widely expressed in fetal and proliferating adult tissues (Kouprina et al, 2005;Wu et al, 2008). The SCFCN2 (Ficolin 2) gene encodes ficolin-2 (L-ficolin), which regulates innate immunity (Munthe-Fog et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation